2013
DOI: 10.4238/2013.december.16.6
|View full text |Cite
|
Sign up to set email alerts
|

Allelic database and divergence among Psidium accessions by using microsatellite markers

Abstract: ABSTRACT. This study aimed to investigate the genetic variability among guava accessions and wild Psidium species of the Embrapa Semiárido germplasm collection by using microsatellite loci to guide genetic resources and breeding programs, emphasizing crosses between guava and other Psidium species. DNA was extracted using the 2X CTAB method, and polymerase chain reaction products were analyzed on 6% denatured polyacrylamide gels stained with silver nitrate. The unweighted pair-group method using arithmetic ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
2
12
1
Order By: Relevance
“…The largest number of accessions were clustered in group I, comprising 44 of the 53 accessions, formed exclusively by guava accessions. The same grouping pattern was observed by da Costa and Santos (2013) based on microsatellite markers and Briceño et al (2010) among Venezuelan accessions of guava and other species of Psidium such as P. guineense. The highest similarity (100%) was observed among the accessions GUA62BA and GUA109RS collected in different regions, Antonio Gonçalves, BA, and Pelotas, RS, respectively.…”
Section: Similarity Genetic Based On Dendrogram Of Jaccard Coefficientsupporting
confidence: 51%
See 4 more Smart Citations
“…The largest number of accessions were clustered in group I, comprising 44 of the 53 accessions, formed exclusively by guava accessions. The same grouping pattern was observed by da Costa and Santos (2013) based on microsatellite markers and Briceño et al (2010) among Venezuelan accessions of guava and other species of Psidium such as P. guineense. The highest similarity (100%) was observed among the accessions GUA62BA and GUA109RS collected in different regions, Antonio Gonçalves, BA, and Pelotas, RS, respectively.…”
Section: Similarity Genetic Based On Dendrogram Of Jaccard Coefficientsupporting
confidence: 51%
“…The similarity among accessions ranged from 0.58 to 1.00 reflecting the existence of high genetic variability among studied accessions. High genetic variability was also reported by da Costa and Santos (2013) among the 61 Psidium accessions of that same collection evaluated by microsatellite marker. Corrêa et al (2011) also reported high genetic variability among 88 Psidium accessions, with similarities ranging from 0.28 to 0.98 based on AFLP markers.…”
Section: Similarity Genetic Based On Dendrogram Of Jaccard Coefficientmentioning
confidence: 76%
See 3 more Smart Citations